Single and Combined Effect of Mild-Heat Treatment and Alginate Coatings on Quality Preservation of Minimally Processed Bunching Green Onions - Medina Jaramillo, Carolina (2022)
Bunching green onion is an Allium species that has been widely used in food flavorings and seasonings. This vegetable experiences a rapid loss of quality during storage due to physiological changes and microbial spoilage. In the current work, the single and combined effect of mild-heat treatment (55 °C for 60 s) and alginate edible coatings on the quality preservation of minimally processed bunching green onions was studied. Control and treated samples were stored at 4 °C for 15 days and examined periodically in terms of their respiration rate, weight loss, pH, soluble solids content, firmness, total polyphenol content, antioxidant activity, microbial count, decay ratio, and overall visual quality. The results showed that the combination of mild heat and alginate edible coatings was the most effective approach to slow down the respiration rate and the incidence of decay in the minimally processed bunching green onions. In addition, the treatments with alginate coating alone or combined with mild-heat treatment showed the best performance for maintaining the overall visual quality of the products during the storage.